Application Analysis: Unit Price Contract System In The Procurement Of Goods And Services At Pt Xyz - Windriya, Anafil; Junaidi, Wahyu; Mashudi, Mashudi; Fauziah, Luluk; Sukoco, Johan Bhimo (Universitas Diponegoro, 2022)
This applied research describe how the process of procurement of goods and services at PT. XYZ. This research is descriptive qualitative research where the method used is a literacy study to find out the previous research, then observation, interview, and observation of document data. Selection of good and services providers at PT. XYZ is done by way of Unit Price Contract (UPC). The stages of the procurement of good and services in UPC system include two stages, at the first stage is carried out to select the procurement participant administratively. The second stage is determining the winner of the UPC partner. In its implementation, the procurement of good and services at PT. XYZ rarely find significant obstacles.